Meniscus-guided coating of organic crystalline thin films for high-performance organic field-effect transistors. Issue 27 (26th June 2020) - Lu, Zhengjun; Wang, Chaoqiang; Deng, Wei; Achille, Malo Tehinke; Jie, Jiansheng; Zhang, Xiujuan
Abstract : In this review, recently reported strategies applied to control the morphology, molecule packing, and orientation of organic semiconductors thin films in the context of meniscus-guided coating techniques are summarized and discussed. Abstract : Organic semiconductors (OSCs) are promising materials for low-cost and large-area electronic devices because they can be processed from solution employing scalable and high-throughput meniscus-guided coating (MGC) techniques. Control over morphology and crystallinity of OSC thin films during MGC are one of the major challenges for achieving high-performance organic electronics toward real-world applications. In this review, we introduce and describe a series of representative MGC techniques that are used in the deposition of small-molecule OSC thin films, and the advantages and limitations of the different MGC methods are discussed. Further, we highlight recently reported strategies applied to control the morphology, molecular packing, and orientation of OSC thin films in the context of MGC techniques, and their impacts on the electronic properties of the resulting organic field-effect transistors (OFETs) are discussed. In addition, the underlying mechanisms of these strategies have been outlined, which gives us insight into how to tune the relevant parameters of MGC techniques to achieve the desired performance of OFETs. Finally, this review provides a comprehensive overview of the current challenges and opportunities in the field of OFETs, aiming to promote the future development of the small-molecule OSCs for large-area thin-film electronics.